Enrollment of students with disabilities in charter schools: Contemporary national and state level findings - Lucy Barnard-Brak; Marcelo Schmidt; M. Hassan Almekdash (Education Policy Analysis Archives, 2018)
There is no national study examining the rate of enrollment of students with disabilities in charter schools. We examined whether students with disabilities were significantly less likely to enroll in charter schools as compared to non-charter public schools accounting for state level variation using data for the entire national population. We utilized data from the Civil Rights Data Collection under the U.S. Department of Education for the 2011-2012 and 2013-2014 academic years. These nationwide and contemporary data provided school-level numbers of students with disabilities receiving special education services under the Individuals with Disabilities Education Act (IDEA) and charter school status. We performed hierarchical linear modeling to examine for differences in the percentages of students with disabilities under IDEA between charter and non-charter schools, which revealed significantly less students with disabilities enrolled in charter schools at the national and state level. Additionally, we identified and ranked states according to the degree of discrepancy in the percentages of students with disabilities under IDEA between charter and non-charter schools.